Prevalence of Low and High BMI in Patients with Infertility - Karoline Riess; Anna Lena Zippl; Lena Reh; Katharina Feil; Bettina Toth (IMR Press, 2023)
Background: The number of individuals who are underweight as well as overweight is increasing worldwide and is known to lead to menstrual disorders and subfertility. Data regarding the prevalence of infertility in Austrian women are lacking. This study aimed to determine the prevalence of a pathologically low and high body mass index (BMI) in Austrian patients with infertility and to evaluate the live birth rate (LBR) after assisted reproductive technologies (ARTs) compared with normal weight patients. Methods: A total of 585 couples with infertility who sought treatment at a single center between April 2017 and April 2019 were included in this retrospective study. The patients were categorized into study group 1 (BMI <19 kg/m2, n = 35), study group 2 (BMI >30 kg/m2, n = 40), and control group (BMI 19-30 kg/m2, n = 95. They were randomly selected from the n = 522 women within these BMI values). Results: The prevalence rates of BMI <19 kg/m2 and BMI >30 kg/m2 were 5.9% and 6.7%, respectively. Baseline clinical and laboratory characteristics as well as the prevalence of pathospermia in their male partners were similar in all study groups. In women undergoing ART (n = 112), LBR was comparable between the study groups (27.3% vs. 31.9% and 22.2%, p = 0.4). Conclusions: The prevalence of low and high BMI in Austrian patients seeking fertility treatment was almost 13%. Although LBR was not reduced, physicians should be more attentive to the BMI values of patients with infertility because pregnancy-related complications are linked to being underweight and obese.